Corporate Finance Practices in Nepal - Chhetri, Raju Basnet (KIC International Journal of Social Science and Management, 2022)
The objective of the study is to explore the practises of capital budgeting, cost of capital, capital structure , and dividend policy adopted by firms in Nepal and to examine whether the practises differ with respect to various demographic variables like firms size, sector, and leverage. The study follows quantitative approach and descriptive research design. Survey was conducted during the month of July and August, 2020 to a population of 978 Nepalese firms with a response rate of nearly 10.33 per cent. The findings on capital budgeting practises of corporate Nepal show a strong preference for non-discounted methods like break even analysis and profitability. The majority of respondents use a WACC as an appropriate discount rate when evaluating any potential investment decision. The scenario analysis and sensitivity analysis of the most widely used techniques for project risk analysis. The Nepalese firms calculate their cost of equity based on regulatory requirement followed by investors requirements. Debt from financial institutions is the most preferred source of finance almost 80% of Nepalese firms have target dividend payout ratio and majority of firms focus on absolute level of dividend than dividend changes.